Factors causing the ineffectiveness of Good Corporate Governance in preventing Corruption in State-Owned Enterprises (Komisi Pemberantasan Korupsi, 2022)
This study aims to provide a brief report and analyze the ineffectiveness of Good Corporate Governance (GCG) in preventing corruption in State-Owned Enterprises (BUMN). This study uses qualitative research methods with data collection through in-depth interviews. Our findings show that Communication Factors, Resource Factors, Disposition Factors (attitudes), and Bureaucratic Factors affect the ineffectiveness of GCG in preventing corruption in BUMN. BUMN implements a gratification control program to prevent corruption by establishing a Gratification Control Unit (UPG), which functions as a service and information unit (help desk) for gratification control. In addition, the company also provides a whistleblowing system. BUMN employees/officials and the public who wish to report an action that indicates a violation within the BUMN environment can report it through this system. However, the program has not been effective in reducing and eliminating the corrupt behavior of BUMN employees/officials due to the lack of leadership, integrity, and values from BUMN employees/officials in preventing corruption. UPG also does not focus on preventing corruption. In addition, policy implementers often fail in carrying out their duties because of the shyness and fear of implementing corruption control policies.